Effects of spontaneously generated coherence on two-photon correlation in a double-cascade scheme - Ooi, Chong Heng Raymond (2007)
We study the effect of spontaneously generated coherence (SGC) on two-photon correlation in a double-cascade scheme. An analytical expression for two-photon correlation is obtained and analyzed. The SGC and asymmetry in the two cascade channels provide a "sinelike" interference term that distorts the profile of the correlation. We show that the SGC term contains nonclassical features that are identical to the spontaneous Raman electromagnetic-induced transparency scheme which shows antibunching. Yet the correlation shows bunching instead of antibunching, and this is explained. We consider all possible transitions and find that photon antibunching is not possible in the double-cascade scheme.